2021
DOI: 10.1007/978-3-030-69963-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Stress Detection with Deep Learning Approaches Using Physiological Signals

Abstract: The problem of stress detection and classification has attracted a lot of attention in the past decade. It has been tackled with mainly two different approaches, where signals were either collected in ambulatory settings, which can be limited to the period of presence in the hospital, or in continuous mode in the field. A sensor-based continuous measurement of stress in daily life has a potential to increase awareness of patterns of stress occurrence. In this work, we first present a data-flow infrastructure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In a separate study, Li et al [30] combined computer usage with HR and HRV data, achieving a prediction accuracy of 71% for eustress, whereas our model reported an accuracy of 88%. Additionally, a study focused on detecting distress events using an ML model based on EDA and BVP attained an F 1 -score of 0.71 [42], compared to our model's F 1 -score of 0.85.…”
Section: Predicting Mood Stress Eustress and Distressmentioning
confidence: 86%
“…In a separate study, Li et al [30] combined computer usage with HR and HRV data, achieving a prediction accuracy of 71% for eustress, whereas our model reported an accuracy of 88%. Additionally, a study focused on detecting distress events using an ML model based on EDA and BVP attained an F 1 -score of 0.71 [42], compared to our model's F 1 -score of 0.85.…”
Section: Predicting Mood Stress Eustress and Distressmentioning
confidence: 86%
“…The original released data contains anxiety labels that were reported in a 5-point scale by subjects. Following the setting in [10], we calculated the z-score of labels for each participant separately, and marked labels below the personalized average as negative (0) and labels above the mean as positive (1). We used 2 hours of the data (5 minutes x 24 steps) to infer upcoming anxiety labels.…”
Section: A Datasetmentioning
confidence: 99%
“…Rising statistics like this has led to an increase in research on mental health, including mental health and well-being prediction using physiological signals over the past couple of years. Several authors research on predicting stress levels, and various mental health conditions using data collected both in clinical settings and in the wild [1], [7], [30], [31], [36], [39].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study used feature selection to reduce the dimensionality of physiological and behavioural data for stress detection and found that the reduced dataset yielded similar performance to the full dataset [19]. Another study used a combination of feature selection and deep learning techniques for stress detection and found that the selected features improved the accuracy and efficiency of the algorithm [20].…”
Section: Introductionmentioning
confidence: 99%